Optimising Autologous Breast Reconstruction: Pneumothorax and Pneumomediastinum—A Literature Review and First Reported Case of Pneumomediastinum Following Bilateral DIEP Flap Reconstruction - Akshay Soni; Ishith Seth; Kaiyang Lim; Alexander Phan; Richard J. Ross; Mathew Lee; Warren M. Rozen (Journal of Personalized Medicine, 2026)
Background: Thoracic air complications after autologous breast reconstruction (ABR) are uncommon and incompletely characterised. A personalised perioperative approach requires integration of patient anatomy, reconstructive technique, anaesthetic exposures and the postoperative clinical trajectory rather than reliance on population-level estimates alone. Methods: We report a 41-year-old woman in whom pneumomediastinum was identified after bilateral DIEP flap reconstruction and performed a focused literature review restricted to primary studies of pneumothorax or pneumomediastinum following autologous flap breast reconstruction. Searches across MEDLINE-Ovid, PubMed and Wiley Online Library using predefined MeSH terms were conducted. Data extraction focused on study characteristics, incidence, mechanism of injury, perioperative factors, and management. Results: The patient developed postoperative hypotension and persistent tachycardia, followed by pleuritic chest pain. CT excluded pulmonary embolism and oesophageal perforation but demonstrated Moderate volume pneumomediastinum without pneumothorax. She was managed conservatively and discharged on postoperative day 7. Five primary studies met the eligibility criteria. Study-specific pneumothorax frequencies were 1/463 (0.22%) after rib-sparing free-flap reconstruction, 3/749 (0.4%) after extended latissimus dorsi reconstruction, and 4/180 patients (2.2%; 1.4 per 100 internal mammary vessel dissections). Reported mechanisms included pleural injury during internal mammary vessel dissection, inadvertent puncture during regional anaesthesia, barotrauma under positive-pressure ventilation, and drain-related barotrauma. No previous primary report of pneumomediastinum after autologous flap breast reconstruction was identified. Conclusions: Pneumothorax and pneumomediastinum are uncommon but potentially serious complications of ABR. They are rarely documented postoperatively; however, surgeons and anaesthetists must remain vigilant, particularly during exposure of the internal mammary vessels and airway management. Patient-specific assessment, symptom-directed imaging and multidisciplinary management may support early recognition to prevent morbidity and preserve the outcomes of reconstructive procedures.